2014
DOI: 10.1371/journal.pone.0102966
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D, Vitamin D Binding Protein, and Risk of Colorectal Cancer

Abstract: BackgroundWe previously reported a positive association between serum 25-hydroxyvitamin D (25(OH)D) and colorectal cancer risk. To further elucidate this association, we examined the molar ratio of 25(OH)D to vitamin D binding protein (DBP), the primary 25(OH)D transport protein, and whether DBP modified the association between 25(OH)D and colorectal cancer risk.MethodsIn a nested case-control study within the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study, controls were 1∶1 matched to 416 colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 43 publications
2
38
1
Order By: Relevance
“…Two previous studies have assessed circulating VDBP in relation to CRC incidence. (10, 11) In line with our results, neither of the studies found an association between VDBP and CRC risk. Interestingly, one study of male smokers found that total 25(OH)D was associated with higher risk of CRC among individuals with high VDBP, with no association among those with low VDBP.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Two previous studies have assessed circulating VDBP in relation to CRC incidence. (10, 11) In line with our results, neither of the studies found an association between VDBP and CRC risk. Interestingly, one study of male smokers found that total 25(OH)D was associated with higher risk of CRC among individuals with high VDBP, with no association among those with low VDBP.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, one study of male smokers found that total 25(OH)D was associated with higher risk of CRC among individuals with high VDBP, with no association among those with low VDBP. (11)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in black and white American suggested that polymorphisms in Gc are also associated with the level of DBP protein itself, which in turn affects bioavailability of free vitamin D (Powe et al, 2013). In terms of cancer risk, recent evidences have suggested that DBP level was a risk-modifier of 25(OH) D in colorectal (Anic et al, 2014) and prostate cancer (Weinstein et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two studies (Anic, Weinstein, Mondul, Mannisto, & Albanes, 2014;Weinstein et al, 2015) evaluated the association between DBP and CRC with no significant results. …”
Section: Dbpmentioning
confidence: 99%